A 10-year knowledge mapping of T cells in rheumatoid arthritis: A bibliometric analysis - Yanfang Gao; Yang Liu; Huiqin Hao (Human Vaccines & Immunotherapeutics)
Rheumatoid arthritis (RA) is a chronic inflammatory joint disease of autoimmune origin. T cells play crucial roles in the initiation and progression of RA. Although bibliometric methods have been widely used to synthesize knowledge trajectories across different biomedical fields, it has hardly been used to underscore the knowledge trends in relation to T cell and RA. This study used bibliometric methods to delineate the evolution of research on T cells and RA. Data were sourced from the Web of Science™ Core Collection and were scientometrically analyzed using CiteSpace and VOSviewer. From 2014 to 2023, 7037 papers on T cells and RA were retrieved. The number of annual publications is stable between 600 and 800, and the citation frequency continues to rise. The United States, China, the United Kingdom and Japan were the most productive countries. Karolinska Institute, and Harvard Medical School were the institutions that published the most research papers. Wei W, Cho ML, and Park SH were the most prolific authors. Mclnnes IB and Smolen JS were the most frequently cited authors. The journals with the most articles are Frontiers in Immunology, Arthritis Research & Therapy, and Arthritis & Rheumatology. Current research hotspots include pathogenic factors and targeted biological therapy, immune mechanisms, inflammatory mechanisms, and bone destruction mechanisms. The current research frontiers in this field are gut microbiota, identification, fibroblast-like synoviocytes, biologic therapy, mesenchymal stem cells, and risk. This work provides new insights into the scientific research and clinical application of T cells to develop therapeutic targets for RA.